Teaching concept of bio-battery material: Use of Sweet Potato Peels and Lime Juice Solution - Maulida, Rahma; Daffa, Muhammad Naufal; Nadhira, Shafwa Faza; Hotimah, Alin Parliana; Anggraeni, Sri; Nandiyanto, Asep Bayu Dani; Sudarjat, Hadi (Bumi Publikasi Nusantara, 2022)
Wasted sweet potato peel waste is a classic problem in Indonesia, therefore the use of sweet potato peel as biomass for bio-battery production can be used as a solution to this problem. This study aimed to determine the benefits of sweet potato peels and orange solution as biomass for bio-battery production. The main novelties in this study are (1) Used sweet potato peels as bio-battery Material that have never been used in previous studies. (2) Used sweet potato peel as fixed variable and lime juice as independent variable, and (3) Tested the sweet potato peel and lime juice pasta into the clock. This method is done by smoothing the skin of the sweet potato with the addition of 40 mL of lime solution to form a paste. The lime solution used in this study was 0; 5; 10; 15%. Then measure the voltage of the bio-battery and test the wall clock with the bio-battery. The experimental results showed that the sweet potato peel paste with a lime solution produced the same voltage as an ordinary battery at a concentration of 10% with a value of 1.47 V. The bio-battery with the highest concentration variation is not necessarily the best, that's because the pH value affects the current and voltage. The conclusion of this research is that sweet potato peel and lime solution can be used as electrolytes in bio-battery production with optimal variation of 5 and 10%. This study demonstrates the utilization of sweet potato peel waste as an alternative biomass for bio-battery production.